2013
DOI: 10.1152/ajpendo.00285.2013
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic exercise but not resistance exercise reduces intrahepatic lipid content and visceral fat and improves insulin sensitivity in obese adolescent girls: a randomized controlled trial

Abstract: Lee S, Deldin AR, White D, Kim Y, Libman I, Rivera-Vega M, Kuk JL, Sandoval S, Boesch C, Arslanian S. Aerobic exercise but not resistance exercise reduces intrahepatic lipid content and visceral fat and improves insulin sensitivity in obese adolescent girls: a randomized controlled trial. Am J Physiol Endocrinol Metab 305: E1222-E1229, 2013. First published September 17, 2013; doi:10.1152/ajpendo.00285.2013.-It is unclear whether regular exercise alone (no caloric restriction) is a useful strategy to reduce ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
259
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(272 citation statements)
references
References 39 publications
(45 reference statements)
6
259
2
Order By: Relevance
“…1 H-MRS was performed with a 3.0 Tesla MR system (Siemens, Tim Trio, Erlangen, Germany) using a body matrix coil and a spine matrix (Siemens) using our established protocol described elsewhere (Lee et al 2012;Lee et al 2013). Fatty liver was defined as liver fat [(methylene lipid peak/methylene lipid peak + water peak) × 100] ≥ 5.0% as shown previously (Perseghin et al 2006).…”
Section: Liver Fat Content By 1 H-mrsmentioning
confidence: 99%
“…1 H-MRS was performed with a 3.0 Tesla MR system (Siemens, Tim Trio, Erlangen, Germany) using a body matrix coil and a spine matrix (Siemens) using our established protocol described elsewhere (Lee et al 2012;Lee et al 2013). Fatty liver was defined as liver fat [(methylene lipid peak/methylene lipid peak + water peak) × 100] ≥ 5.0% as shown previously (Perseghin et al 2006).…”
Section: Liver Fat Content By 1 H-mrsmentioning
confidence: 99%
“…Thus, exercise training has been applied as the first choice for children who are overweight or obese, but not morbidly obese caused by underlying pathologies (16). Previous studies have reported that exercise training in children with obesity improves their body composition (10,28), cardiovascular function (4,7), and physical fitness (12,13,29). However, there are few studies of the effects of exercise training in obese children aged 5 years.…”
mentioning
confidence: 99%
“…Moreover, despite performing double the training load of the aerobic alone or PRT alone groups, aerobic exercise combined with PRT led to a non-significant reduction in liver fat. A superior hepatic benefit of aerobic exercise training was also demonstrated in obese adolescent girls [12]; however, comparable reductions between aerobic and resistance training have been observed in NAFLD patients with type 2 diabetes [5] and in obese adolescent boys [13].…”
Section: Progressive Resistance Trainingmentioning
confidence: 82%
“…With respect to aerobic exercise, these guidelines promote moderate-intensity cardiorespiratory exercise training for ‡30 min on at least 5 days per week, or vigorous cardiorespiratory exercise training for ‡20 min on 3 days per week, or a combination of both and align with global recommendations for health, fitness and disease prevention [10]. Exercise interventions meeting these guidelines consistently demonstrate reduction in liver fat of 10-43% in patients with NAFLD [5,6,[11][12][13][14][15][16].…”
Section: Aerobic Exercise Trainingmentioning
confidence: 99%
See 1 more Smart Citation